Georg A. Walser, Old Testament Quotations in Hebrews: Studies in Their Textual and Contextual Background (Wissenschaftliche Untersuchungen zum Neuen Testament. 2. Reihe 356; Tübingen: Mohr Siebeck 2013) - Malina, Artur (The Biblical Annals, 2018)
Book review: Georg. A. Walser, Old Testament Quotations in Hebrews: Studies in Their Textual and Contextual Background (Wissenschaftliche Untersuchungen zum Neuen Testament. 2. Reihe 356; Tübingen: Mohr Siebeck 2013). Pp. xiv + 220. DOI: https://doi.org/10.31743/ba.2018.8.2.10